A Tale of Two Universities: Primary Carers Working in Australian Universities - Hodgson, Helen; Bowyer, Dorothea (IGI Global, 2023)
Returning to work after a career break can be challenging, accordingly employers implement a range of policies, practices, and strategies to support and retain working parents. This chapter analyses the work-family policies at two universities in the Australian university sector, through the eyes of academic parents. Grounding the discussion in the Australian industrial relations system, the authors examine the lived experience of academic parents drawing on two separate qualitative studies at two different Australian Universities. Initiatives in place to enhance career progression for academic parents are tested against lived experience. The authors find that policies and strategies need to be overhauled and suggest more feasible ones that universities can implement to enable the academic parent, who is juggling an academic career with parenting, to succeed in the post COVID uncertainty faced by the higher education sector.